2020
DOI: 10.3390/nano10081592
|View full text |Cite
|
Sign up to set email alerts
|

Gated Resonance Energy Transfer (gRET) Controlled by Programmed Death Protein Ligand 1

Abstract: The resonance energy transfer (RET) between an excited fluorescent probe molecule and a plasmonic nanoparticle (AuNP) has been investigated to evaluate the effect of protein molecules on the RET efficiency. We have found that the energy transfer to a functionalized AuNP can be modulated by a sub-monolayer film of programmed death-ligand 1 (PD-L1) protein. The interactions of PD-L1 with AuNP@Cit involve incorporation of the protein in AuNP shell and formation of a submonolayer adsorption film with voids enablin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…We evaluated the affinity with the BSA protein as previously reported to confirm the hapten ability of the silica nanomaterial [ 28 ]. In addition to the methods we have measured, test methods for sensitive protein detection have been recently reported and can be used as a test method for protein adsorption of nanomaterials [ 29 , 30 ]. In this study, the results of the protein binding affinity of silica NPs were observed to easily react with the albumin protein present in a large number in the body, showing almost maximum reactivity in 4 h. This protein binding ability is a very important factor in the haptenization of sensitinogen [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…We evaluated the affinity with the BSA protein as previously reported to confirm the hapten ability of the silica nanomaterial [ 28 ]. In addition to the methods we have measured, test methods for sensitive protein detection have been recently reported and can be used as a test method for protein adsorption of nanomaterials [ 29 , 30 ]. In this study, the results of the protein binding affinity of silica NPs were observed to easily react with the albumin protein present in a large number in the body, showing almost maximum reactivity in 4 h. This protein binding ability is a very important factor in the haptenization of sensitinogen [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al [ 36 ] hypothesized that combining IFN-γ release assay (IGRA) with the tumor necrosis factor-alpha (TNF-α) release assay could differentiate active TB from latent TB infections. Using the ELISPOT assay on peripheral mononuclear cells, the authors reported a higher sensitivity and specificity (89% and 93%) when the IGRA and TNF-α tests were combined, than for IGRA alone [ 20 ]. Although their results appeared to be useful for diagnosing active TB, they got indeterminate results from their negative controls and the number of patients involved in the study is not big enough for drawing clinical conclusions.…”
Section: Conventional Assay Techniquesmentioning
confidence: 99%
“…Given the similarity on the dimensional scale, nanotechnological approaches are the most promising route towards synthetic virus surrogates. Gold nanoparticles (AuNPs) are among the most widely used nanomaterials in biomedical applications, including drug and gene delivery [ 16 , 17 ], imaging/diagnostics [ 18 20 ], and photodynamic/photothermal therapies [ 21 , 22 ]. This ubiquitous utility results from specific features of AuNPs including their outstanding optical and photothermal properties, their high affinity for binding of/to a wide variety of (bio)molecules given their flexible surface chemistry, and the facile control of the synthesis conditions to obtain a wide variety of particles shapes and sizes [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%